PEREMPUAN DAN PENDIDIKAN DALAM PERSPEKTIF HAM - Bahrul Hayat (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2012)
This paper discusses the participation of women education in the perspective of human rights. The research is field study with a sample distribution from elementary school to college with the scope of research on aspects of illiteracy, formal education, and non-formal education. The research showed that the cause of gender disparity in education is closely related to religious, social, economic, cultural, and geographical factors. Although from legal aspect and educational policy, men and women are given equal access, but the various constraints restrict women's struggle to obtain equality of educational opportunities.